Dataset of EEG power integral, spontaneous recurrent seizure and behavioral responses following combination drug therapy in soman-exposed rats - Lucille A. Lumley; Franco Rossetti; Marcio de Araujo Furtado; Brenda Marrero-Rosado; Caroline R. Schultz; Mark K. Schultz; Jerome Niquet; Claude G. Wasterlain (Data in Brief, 2019)
This article investigated the efficacy of the combination of antiepileptic drug therapy in protecting against soman-induced seizure severity, epileptogenesis and performance deficits. Adult male rats with implanted telemetry transmitters for continuous recording of electroencephalographic (EEG) activity were exposed to soman and treated with atropine sulfate and the oxime HI-6 one minute after soman exposure and with midazolam, ketamine and/or valproic acid 40 min after seizure onset. Rats exposed to soman and treated with medical countermeasures were evaluated for survival, seizure severity, the development of spontaneous recurrent seizure and performance deficits; combination anti-epileptic drug therapy was compared with midazolam monotherapy. Telemetry transmitters were used to record EEG activity, and a customized MATLAB algorithm was used to analyze the telemetry data. Survival data, EEG power integral data, spontaneous recurrent seizure data and behavioral data are illustrated in figures and included as raw data. In addition, edf files of one month telemetry recordings from soman-exposed rats treated with delayed midazolam are provided as supplementary materials. Data presented in this article are related to research articles “Rational Polytherapy in the Treatment of Cholinergic Seizures” [1] and “Early polytherapy for benzodiazepine-refractory status epilepticus [4]. Keywords: Soman, Ketamine, Midazolam, Valproic acid, Chemical warfare nerve agent, Epileptogenesis, Status epilepticus